Physical Activity and Nutritional Influence on Immune Function: An Important Strategy to Improve Immunity and Health Status - Shao, Tianyi; Verma, Henu Kumar; Pande, Babita; Costanzo, Vincenzo; Ye, Weibing; Cai, Yuyan; Bhaskar, L. V. K. S. (Frontiers in Physiology, 2021)
Physical activity (PA) and nutrition are the essential components of a healthy lifestyle, as they can influences energy balance, promote functional ability of various systems and improve immunity. Infections and their associated symptoms are the common and frequent challenges to human health that are causing severe economic and social consequences around the world. During aging, human immune system undergoes dramatic aging-related changes/dysfunctions known as immunosenescence. Clinically, immunosenescence refers to the gradual deterioration of immune system that increases exposure to infections, and reduces vaccine efficacy. Such phenomenon is linked to impaired immune responses that lead to dysfunction of multiple organs. While lack of physical activity, progressive loss of muscle mass, and concomitant decline in muscle strength facilitate immunosenescence and inflammation. In the present review, we have discussed the role of nutrition and PA, which can boost the immune system alone and synergistically. Evidence suggests that long-term PA is beneficial in improving immune system and preventing various infections. We further discussed several nutritional strategies for improving the immune system. Unfortunately, the available evidence shows conflicting results. In terms of interaction with food intake, PA does not tend to increase energy intake during a short time course. However, overcoming nutritional deficiencies appears to be the most practical recommendation. Through the balanced nutritious diet intake one can fulfill the bodily requirement of optimal nutrition that significantly impacts the immune system. Supplementation of a single nutrient as food is generally not advisable. Rather incorporating various fruits and vegetables, whole grains, proteins and probiotics may ensure adequate nutrients intake. Therefore, multi-nutrient supplements may benefit people having deficiency in spite of sufficient diet. Along with PA, supplementation of probiotics, bovine colostrum, plant-derived products and functional foods may provide additional benefits in improving the immune system.